2015
DOI: 10.1161/atvbaha.114.304857
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Molecular Ultrasound Monitoring of Vessel Healing After Intravascular Surgical Procedures in a Preclinical Setup

Abstract: Objective— Cardiovascular interventions induce damage to the vessel wall making antithrombotic therapy inevitable until complete endothelial recovery. Without a method to accurately determine the endothelial status, many patients undergo prolonged anticoagulation therapy, denying them any invasive medical procedures, such as surgical operations and dental interventions. Therefore, we aim to introduce molecular ultrasound imaging of the vascular cell adhesion molecule (VCAM)-1 using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
(32 reference statements)
1
25
0
1
Order By: Relevance
“…Compared with other modalities, acquisition of UBM images is time efficient and does not need to use contrast agents . Another advantage is the real‐time in vivo acquisition of detailed morphologic and physiologic data, which can be processed further with advanced software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other modalities, acquisition of UBM images is time efficient and does not need to use contrast agents . Another advantage is the real‐time in vivo acquisition of detailed morphologic and physiologic data, which can be processed further with advanced software.…”
Section: Discussionmentioning
confidence: 99%
“…New methods for the in vivo visualization of arterial wall healing have been reported; these have targeted the increased vascular permeability in areas lacking an intact endothelium using contrast‐enhanced magnetic resonance imaging . Contrast‐enhanced ultrasound (US) has also been used to visualize the arterial healing process by targeting specific molecules in activated endothelial cells and vascular smooth muscle cells, such as α v β 3 ‐integrin and vascular cell adhesion molecule‐1 . However, all of these methods share the same limitation of being dependent on vascular access or the use of contrast agents.…”
mentioning
confidence: 99%
“…In future experiments, adhesion molecule expression on the endothelium could be assessed by immunofluorescence imaging. With the use of 2‐photon laser‐scanning microscopy, it should be (after staining and fixation) possible to identify the endothelial/vascular aspect in 3 dimensions in intact liver tissue and assess the presence and density of adhesion molecules, such as ICAM‐1 and VCAM‐1 …”
Section: Discussionmentioning
confidence: 99%
“…With the use of 2-photon laser-scanning microscopy, it should be (after staining and fixation) possible to identify the endothelial/vascular aspect in 3 dimensions in intact liver tissue and assess the presence and density of adhesion molecules, such as ICAM-1 and VCAM-1. 31 Lastly, we did not assess liver tissue damage due to administration of the PFH-loaded macrophage suspension. Dirven et al 14 reported liver lesions on microbubble administration, but only after 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other available anatomic imaging methods such as ultrasound, 74 magnetic resonance (MR) or computed tomography, PET imaging 7577 has the advantageous ability to visualize minuscule concentrations of tracers that target specific molecular process. PET vascular inflammation imaging with fluorodeoxyglucose (FDG) has become important in atherosclerosis research, 78 owing to FDG's accumulation in cells with glycolytic rate.…”
Section: Integration Of Imagingmentioning
confidence: 99%